2012
DOI: 10.1159/000337224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cognitive and Aerobic Training Intervention on Older Adults with Mild or No Cognitive Impairment: A Derivative Study of the Nakajima Project

Abstract: Background: An increasing elderly population in Japan requires effective cognitive intervention programs for dementia. This study demonstrates the effectiveness of such programs for older adults. Methods: The participants were local community-dwelling non-demented older adults and adults with mild cognitive impairment who underwent executive function and group aerobic training. In addition, a non-intervention group participated in activity sessions involving handicraft, Skutt ball matches, and cooking. The fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 37 publications
3
34
1
3
Order By: Relevance
“…The effect of aerobic exercise and physical activity has been reported to improve episodic memory in many studies. 4,20 In the present study, depression (GDS) tended to improve, suggesting that physical activity reduces depression in older adults. Physical activity has effects on anxiety, social dysfunction and depression, as well as somatic symptoms.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The effect of aerobic exercise and physical activity has been reported to improve episodic memory in many studies. 4,20 In the present study, depression (GDS) tended to improve, suggesting that physical activity reduces depression in older adults. Physical activity has effects on anxiety, social dysfunction and depression, as well as somatic symptoms.…”
Section: Discussionsupporting
confidence: 49%
“…In the present study, subjective memory complaints (Questionnaire for Subjective Memory Complaint) decreased significantly, meaning that participants felt forgetful less frequently after the intervention. The effect of aerobic exercise and physical activity has been reported to improve episodic memory in many studies …”
Section: Discussionmentioning
confidence: 99%
“…Identifying these patients very early in the disease course is critical to implementing interventions and cognitive rehabilitation. In fact, work has shown that patients with aMCI can improve cognition and functional status when interventions are applied early in the disease course [88,89]. …”
Section: Conclusion and Clinical Considerationsmentioning
confidence: 99%
“…A study in Kyoto compared executive function and aerobic training with standard occupational therapy in non-demented older adults. The participants in both intervention groups showed better memory performance over usual care (Sugano et al, 2012). A study of 12-week computer-based memory and attention training in MCI suggested benefits in episodic memory with effects persisted at six months (Herrera, Chambon, Michel, Paban, & Alescio-Lautier, 2012).…”
Section: Cognitive Trainingmentioning
confidence: 89%